2019
DOI: 10.2147/opth.s192424
|View full text |Cite
|
Sign up to set email alerts
|

<p>Functional outcome of repeat Descemet membrane endothelial keratoplasty (DMEK) for corneal decompensation following graft failure after primary DMEK</p>

Abstract: PurposeTo evaluate if repeat Descemet membrane endothelial keratoplasty (DMEK) is appropriate to achieve functional improvements in patients with corneal decompensation from secondary graft failure after primary DMEK.MethodsThis is a retrospective monocentric cohort study including 13 eyes of 13 patients with repeat DMEK for corneal decompensation following primary DMEK. Eyes with primary DMEK only and comparable preoperative corrected distance visual acuity (CDVA) served as control. Main outcome parameter was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 15 publications
(24 reference statements)
1
12
0
1
Order By: Relevance
“…After two years, 86% of patients achieved a BCVA of at least 20/40. Agha et al 78 showed that BCVA was similar in eyes undergoing re-DMEK or primary DMEK, and BCVA improved after surgery in both groups.…”
Section: Repeat Endothelial Keratoplasty or Penetrating Keratoplasty ...mentioning
confidence: 99%
“…After two years, 86% of patients achieved a BCVA of at least 20/40. Agha et al 78 showed that BCVA was similar in eyes undergoing re-DMEK or primary DMEK, and BCVA improved after surgery in both groups.…”
Section: Repeat Endothelial Keratoplasty or Penetrating Keratoplasty ...mentioning
confidence: 99%
“…Bei Patienten mit rascher Reoperation, durchgeführt, um die Dauer der zentralen Hornhautdekompensation zu minimieren, entsprachen die Visusergebnisse mit sekundärer DMEK den Visusergebnissen mit primärer DMEK 16 , 29 , 30 .…”
Section: Dmek Nach Dmek/dsaekunclassified
“…In patients with rapid repeat surgery, performed to minimize the duration of central corneal decompensation, visual outcomes with secondary DMEK were equivalent to visual outcomes with primary DMEK [16,29,30].…”
Section: Dmek After Dmek/dsaekmentioning
confidence: 99%
“…Until recently, repeated EK was mainly performed for graft failure after PKP, but the number of cases of repeated EK has gradually increased [1,6]. In particular, in the case of graft failure after primary DMEK, repeat DMEK can be performed if there are no contraindications for EK, such as stromal scarring and opaci cation [1,7]. Nevertheless, repeated DMEK can cause severe problems, such as failure to remove the previous graft.…”
Section: Introductionmentioning
confidence: 99%